The Effect of Good Corporate Governance Mechanisms on Return On Assets in Healthcare Companies for the Period 2018-2022: Pengaruh Mekanisme Good Corporate Governance Terhadap Return On Assets Pada Perusahaan Healthcare Periode 2018-2022 - Noer Ridha, Noorsyah Adi; Mufti, Fauzan Ali (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study aims to determine the effect of the Good Corporate Governance Mechanism proxied by the board of directors (DD), the proportion of women on the board of commissioners (PWDK), the proportion of women on the board of directors (PWDD), and the proportion of women on the audit committee (PWKA) on ROA in healthcare companies listed on the Indonesian Sharia Stock Index (ISSI) for the period 2018-2022. The population in this study used purposive sampling method with secondary data obtained from the annual reports of healthcare companies listed on ISSI for the period 2018-2022. This study uses descriptive analysis and panel data regression analysis using the E-views 12 analysis tool. From this study, it was found that the DD and PWDD variables had an effect on ROA while PWDK and PWKA had no effect on ROA.